2016
DOI: 10.1007/s12551-016-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule studies of high-mobility group B architectural DNA bending proteins

Abstract: Protein–DNA interactions can be characterized and quantified using single molecule methods such as optical tweezers, magnetic tweezers, atomic force microscopy, and fluorescence imaging. In this review, we discuss studies that characterize the binding of high-mobility group B (HMGB) architectural proteins to single DNA molecules. We show how these studies are able to extract quantitative information regarding equilibrium binding as well as non-equilibrium binding kinetics. HMGB proteins play critical but poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 124 publications
(238 reference statements)
2
54
0
Order By: Relevance
“…A total of 72,201,113 raw reads (35,207,345 for SAMP8 and 36,993,768 for SAMR1) were generated. After removal of low-quality and adapter sequences, 71,044,988 clean reads (36,446,427 for SAMR1 and 34,598,561 for SAMP8) were obtained. We filtered the preceding results based on length (18-35 nt).…”
Section: Overview Of Mirna-seqmentioning
confidence: 99%
“…A total of 72,201,113 raw reads (35,207,345 for SAMP8 and 36,993,768 for SAMR1) were generated. After removal of low-quality and adapter sequences, 71,044,988 clean reads (36,446,427 for SAMR1 and 34,598,561 for SAMP8) were obtained. We filtered the preceding results based on length (18-35 nt).…”
Section: Overview Of Mirna-seqmentioning
confidence: 99%
“…TFAM belongs to the high-mobility-group (HMG) box family of DNA binding proteins (6,7), and consists of two HMG box domains (HMG1 and HMG2) separated by a linker, coupled to a C-terminal tail via HMG2 (Figure 1). TFAM is essential for initiating transcription of mitochondrial DNA (mtDNA) by specifically recognizing the light-strand and heavy-strand promoters of the mitochondrial genome (8–12).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies, including measurements of the kind reported here, are needed to carefully flesh out the dynamics and distributions of these ubiquitous DNA benders. 99 Our observation of partially bent specific conformations in IHF-DNA complexes also provide structural insights into the underlying mechanism for the "facilitated dissociation"…”
Section: Discussionmentioning
confidence: 74%